Graphene-based ordered framework with a diverse range of carbon polygons formed in zeolite nanochannels. (April 2018) - Nishihara, Hirotomo; Fujimoto, Hiroyuki; Itoi, Hiroyuki; Nomura, Keita; Tanaka, Hideki; Miyahara, Minoru T.; Bonnaud, Patrick A.; Miura, Ryuji; Suzuki, Ai; Miyamoto, Naoto; Hatakeyama, Nozomu; Miyamoto, Akira; et al.
Abstract: With the aim of understanding three-dimensional graphene-based frameworks in detail, a realistic structure model of zeolite-templated carbon (ZTC) is constructed by using computer simulation, and its simulated physical properties are compared with experimental data. The proposed structure model provides the insight into a unique X-ray diffraction pattern of ZTC: disordered building units comprised of curved and non-stacked graphene fragments are connected along the ordered zeolite nanochannels, forming a long-range structure order derived from zeolite (111) and (220) planes. Though ZTC is one of the superporous carbons with a very large Brunauer–Emmett–Teller (BET) surface area (3935 m 2  g −1 ), the simulation study indicates a possibility to achieve further higher BET surface area up to 4845 m 2  g −1 . Moreover, the presence of carbon polygons other than hexagon in graphene matrices is analyzed by a high-resolution pair distribution function obtained from neutron diffraction measurement. The comparison between experimental data and simulation suggests that ZTC framework contains a diverse range of carbon polygons such as hexagons, heptagons and octagons, while pentagons are minor. Such distribution of carbon polygons demonstrates interesting similarity between the real three-dimensional graphene-based framework and imaginary ones like Mackay crystals and carbon Schwarzites. Graphical abstract: Image 1